Balancing the costs of carbon gain and water transport: testing a new theoretical framework for plant functional ecology - I. Colin Prentice; Ning Dong; Sean M. Gleason; Vincent Maire; Ian J. Wright (Ecology Letters, 2014)
A novel framework is presented for the analysis of ecophysiological field measurements and modelling. The hypothesis ‘ leaves minimise the summed unit costs of transpiration and carboxylation ’ predicts leaf‐internal/ambient CO 2 ratios ( c i /c a ) and slopes of maximum carboxylation rate ( V cmax ) or leaf nitrogen ( N area ) vs . stomatal conductance. Analysis of data on woody species from contrasting climates (cold‐hot, dry‐wet) yielded steeper slopes and lower mean c i /c a ratios at the dry or cold sites than at the wet or hot sites. High atmospheric vapour pressure deficit implies low c i /c a in dry climates. High water viscosity (more costly transport) and low photorespiration (less costly photosynthesis) imply low c i /c a in cold climates. Observed site‐mean c i /c a shifts are predicted quantitatively for temperature contrasts (by photorespiration plus viscosity effects) and approximately for aridity contrasts. The theory explains the dependency of c i /c a ratios on temperature and vapour pressure deficit, and observed relationships of leaf δ 13 C and N area to aridity.